PENGARUH PERILAKU WORK FROM HOME DAN STRES KERJA TERHADAP KINERJA PEGAWAI LEMBAGA PENJAMIN SIMPANAN - Azzahra, Anindita; Handaru, Agung Wahyu; Wolor, Christian Wiradendi (Jurnal Pijar, 2023)
The objectives of this study were: 1) To determine and analyze the effect of work from home behavior on employee performance. 2) To determine and analyze the effect of work stress on employee performance. 3) To determine and analyze the effect of work from home behavior and work stress on employee performance. Research using quantitative methods. This research was conducted on 140 staff position employees. The data collection technique used a survey method through distributing questionnaires and processed using SPSS version 26 software: 1) Work from home behavior is positive and significant to employee performance. 2) Work stress has a positive and significant effect on employee performance. 3) There is a positive and significant influence between work from home behavior and work stress on employee performance.